Approaches to the Industry Council Idea in the United States - Schnepp, Gerald; Morello, Isabelle (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1954)
SummaryThere is no exact Industry Council System in the United States, but there are in industry, agriculture and professions some real efforts of cooperative activity and integration which lead to approximations of the System itself as described in the first part of this article. Then, a specimen of those approaches is studied. The readers will find interest in learning about the constitution and functioning of that organization which accompanied by others alike, are walking toward the realization of the Industry Council System.